Handbook on health inequality monitoring : with a special focus on low- and middle-income countries (WHO GenevaCH, 2013)
Provides an overview for health inequality monitoring within low- and middle-income countries, and acts as a resource for those involved in spearheading, improving or sustaining monitoring systems.
Keywords: HEALTH SERVICES